Cloning, expression, and characterization of Aureobasidium melanogenum lipase in Pichia pastoris. Issue 11 (1st November 2016) - Wongwatanapaiboon, Jinaporn; Klinbunga, Sirawut; Ruangchainikom, Chalermchai; Thummadetsak, Gamgarn; Chulalaksananukul, Suphang; Marty, Alain; Chulalaksananukul, Warawut
Abstract: cDNA of Aureobasidium melanogenum lipase comprises 1254 bp encoding 417 amino acids, whereas genomic DNA of lipase comprises 1311 bp with one intron (57 bp). The lipase gene contains a putative signal peptide encoding 26 amino acids. The A. melanogenum lipase gene was successfully expressed in Pichia pastoris . Recombinant lipase in an inducible expression system showed the highest lipase activity of 3.8 U/mL after six days of 2% v/v methanol induction. The molecular mass of purified recombinant lipase was estimated as 39 kDa using SDS-PAGE. Optimal lipase activity was observed at 35–37 °C and pH 7.0 using p -nitrophenyl laurate as the substrate. Lipase activity was enhanced by Mg 2+, Mn 2+, Li +, Ca 2+, Ni 2+, CHAPS, DTT, and EDTA and inhibited by Hg 2+, Ag +, SDS, Tween 20, and Triton X-100. The addition of 10% v/v acetone, DMSO, p -xylene, and octanol increased lipase activity, whereas that of propanol and butanol strongly inhibited it. Graphical abstract: : Lipase activity of Aureobasidium melanogenum lipase expressed in Pichia pastoris using inducible and constitutive expression system.